Analysis of the Role of Income Audit in Internal Control: Evidence from the Hospitality Sector in Bali - Putri, Ni Luh Asriani; Damayanti, Titien; Septiviari, Anak Agung Istri M. (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
This study aims to analyze the role of income audit in internal control at Courtyard by Marriott Bali Nusa Dua Resort. The approach used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The theoretical framework used in this study refers to the internal control component and fraud triangle theory which includes three elements: pressure, opportunity, and rationalization. The results of the study shed light that income audit plays an active and significant role in ensuring the accuracy of hotel revenue reports through the process of daily transaction verification, system matching, and formal short/over reporting. The four components of internal control have been implemented well, and the three elements of triangle fraud have also been effectively controlled. Based on the 15 observation indicators used, all of them were declared to be implemented, and the effectiveness of internal control reached 100%. This research contributes to hotel management in maintaining an accountable internal control system, as well as providing strategic recommendations for continuous improvement in the implementation of revenue audits.